Faith and Disaster Resilience: What can Islamic Education Teach Children to Help Prepare Them for A Disaster? - Husni Rahiem, Maila Dinia (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2018)
AbstractChildren used their internal mechanisms, including faith, in coping and bouncing back after a disaster. In this paper, researcher examines the role of faith in building more resilient communities, and also how Islamic education at school can be used to help teach children to be better prepared for a disaster. The research suggests that Islamic education could be used to increase students hope after a disaster, to seek prayer as a source of strength and peace, to see the essential role of Muslim clergies in disaster recovery, and to see how some religious practices need to be understood in better ways. Qualitative narrative research was used as the method of inquiry with the primary source of data coming from interviews. There are 27 child survivors being interviewed. All those interviews were audio-recorded and transcribed, then the transcripts were analysed to find any emerging themes.AbstrakBeberapa anak menggunakan mekanisme internal mereka, termasuk iman, dalam mengatasi dan bangkit kembali setelah bencana. Dalam makalah ini, peneliti meneliti peran iman dalam membangun komunitas yang lebih tangguh, dan juga bagaimana pendidikan Islam di sekolah dapat digunakan untuk membantu mengajar anak-anak agar lebih siap menghadapi bencana. Penelitian ini menunjukkan bahwa pendidikan Islam dapat digunakan untuk meningkatkan harapan pelajar setelah bencana, untuk menjadikan doa sebagai sumber kekuatan dan perdamaian, untuk melihat peran penting para ulama Muslim dalam pemulihan bencana, dan untuk melihat bagaimana beberapa praktik keagamaan perlu dilakukan. dipahami dengan cara yang lebih baik. Penelitian naratif kualitatif digunakan sebagai metode penyelidikan dengan sumber data utama yang berasal dari wawancara. Ada 27 anak yang selamat yang diwawancarai. Semua wawancara itu direkam dan ditranskripsi, kemudian transkrip dianalisis untuk menemukan topik yang tampak. How to Cite : Rahiem, M. D. H. (2018). Faith and Disaster Resilience: What can Islamic Education Teach Children to Help Prepare Them for a Disaster?. TARBIYA: Journal of Education in Muslim Society, 5(2), 178-192. doi:10.15408/tjems.v5i2.9964.